Editor's Note. - Williams, Raymond Brady (Teaching Theology & Religion)
Focuses on the impact of technological changes on education and teaching strategies. Changes in the students' experience, technical abilities and learning styles; Amount of information available through computer assisted information technology; Efforts done to explore the application of the technological advances in education.